Detection of adrenal veins on selective retrograde CT adrenal venography in comparison with digital subtraction angiography in subjects with established diagnosis of one-sided adrenal aldosterone-producing tumor confirmed by adrenal vein sampling, histopathology and clinical course - Higashide, Takashi; Funabashi, Nobusada; Tanaka, Tomoaki; Inoue, Kohei; Kazama, Toshiki; Motoori, Ken; Nagano, Hidekazu; Nakatani, Yukio; Ichikawa, Tomohiko; Takaoka, Hiroyuki; Uehara, Masae; Yokote, Kotaro; et al. (International journal of cardiology, 2013)
Adrenal vein (AV) sampling (AVS) is the diagnostic gold standard for primary aldosteronism (PA), but right-sided AVS is difficult. We compared detection of AVs by selective retrograde CT adrenal venography (SRCTAV) with digital subtraction angiography (DSA). Data on 29 subjects (11 males, mean age 55y) with increased serum aldosterone concentrations (SAC) and a diagnosed right or left aldosterone-producing tumor (APT) by AVS who underwent laparoscopic adrenalectomy were retrospectively analyzed. Before AVS, visualizing AVs was attempted by DSA and SRCTAV (Aquilion). If after the adrenocorticotropic hormone loading test serum cortisol concentration (SCC) from either AV was >200μg/dl, AVS was considered successful. If the SAC/SCC ratio for one side was ≥4 times higher than the other side, we diagnosed a one-sided APT. Left and right AV, respectively, were visualized in 29 (100%) and 22 subjects (76%) by DSA and 29 (100%) and 28 subjects (97%) by SRCTAV, with right-AV detection significantly higher by SRCTAV (p<0.05). Cannulations were regarded successful in 28 subjects having both AVs observed on SRCTAV but not in the remaining subject whose adrenocortical scintigram was positive, however. Adrenalectomy was performed with a diagnosis of adenoma. Among 28 subjects with successful AVS, histopathological diagnoses included adenoma (25), nodular hyperplasia (2) and normal (1). After adrenalectomy, antihypertensive drug usage in 28 patients was reduced or stopped with decreases in SAC (97%). Detection of AV was significantly higher by SRCTAV than DSA, especially on the right side, in 29 subjects diagnosed with one-sided APT.